Engaging with Chaucer : practice, authority, reading - Moseley C. W. R. D. (Berghahn Books, 2021)
Why do we still read and discuss Chaucer? The answer may be simple: he is fun, and he challenges our intelligence and questions our certainties. This collected volume represents an homage to a toweringly great poet, as well as an acknowledgement of the intellectual excitement, challenges, and pleasure that readers owe to him as even today, his poems have the capacity to change the way we engage with fundamental questions of knowledge, understanding, and beauty.